2016
DOI: 10.11648/j.ajep.20160506.17
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Flows Risk Assessment of Effluent Outfalls from Conventional Wet Washed Coffee Refineries in Limu Kosa District of Southwestern Ethiopia

Abstract: Abstract:The objective of this study was to assess the effects of recurrent effluent outfall from conventional wet washed coffee refineries (CWCR) on environmental flows (Eflows) based on the physicochemical parameters & benthos assemblages as biological indicators. The experiment was done using complete randomized design (CRD) with 3 composite replicates at each 24 sampling sites of 4 river water basins. Six sampling sites were selected for physico-chemical & 2 sampling sites were selected for benthos assembl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 8 publications
(12 reference statements)
1
3
1
Order By: Relevance
“…The mean TS, TSS, and turbidity levels of both coffee processing plants were also found high enough to cause pollution ( Table 2 ). Both TS and TSS Values were found similar to previous studies obtained by Mosissa et al 18 such elevated value of TS, TSS, and turbidity in both plant coffee wastewater could be attributed to various solid by-products such as coffee pulp, skin, parchment, and bean can contribute to turbidity. Discharge of solids increases the turbidity of water and causes a long-term demand for oxygen because of the slow hydrolysis rate of the organic fraction of the material.…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations
“…The mean TS, TSS, and turbidity levels of both coffee processing plants were also found high enough to cause pollution ( Table 2 ). Both TS and TSS Values were found similar to previous studies obtained by Mosissa et al 18 such elevated value of TS, TSS, and turbidity in both plant coffee wastewater could be attributed to various solid by-products such as coffee pulp, skin, parchment, and bean can contribute to turbidity. Discharge of solids increases the turbidity of water and causes a long-term demand for oxygen because of the slow hydrolysis rate of the organic fraction of the material.…”
Section: Resultssupporting
confidence: 89%
“…But the abundance and diversity level remained lower than compared with the upper stream sites of the Orsha river which was in line with the study conducted. 18 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The mean effluent of Ammonium (NH 4 + ) concentration from Natural wetland (0.52 ± 0.59 mg/l) were found within the national (Ethiopian) effluent discharge to rivers which is (⩽1 mg/l) .However, the mean effluent in constructed wetland was above the standard discharge limit for rivers. The results show that the mean effluent (0.52 ± 0.59 mg/l ) of natural wetlands was lower (4.99 ± 0.36 ppm) than that reported by Mosissa et al 46 and reported by Bisekwa et al 47 with a mean of 5.55 ± 2.23 mg/l. This might be due to previous studies where wastewater effluents released without any treatment.…”
Section: Resultscontrasting
confidence: 49%